EXPLORING EFL STUDENTS’ AWARENESS OF THE DIFFERENCES BETWEEN AMERICAN AND BRITISH VARIETIES - Achmad Ivansyah Obos; Susilo Susilo; Maria Teodora Ping (Lingua, 2022)
The objectives of this research are to explore how the EFL students aware toward American and British English and to know EFL students’ perception towards both varieties that influence their learning experiences. This qualitative descriptive research conducted the ethnonarrative approach, which were analyzed descriptively through collecting the data, reducing inappropriate data, displaying and concluding data. The results revealed that the way how the EFL students aware toward American and British English were the participants watch television programs to do self-understanding, they learned both varieties in school and took the TOEFL and IELTS exam, they also frequently use American English to make a conversation as their process of socialization. The EFL students’ perception towards both varieties that influence their learning experiences were different. The first participant thought that British English is way much professional, had unique grammatical and vocabularies. While the second participant thought that American English used for daily conversation.